Synthesis of 1-(2-Hydroxy-5-methylphenyl)-5-oxopyrrolidine-3-carboxylic Acid Derivatives as a Promising Scaffold Against Disease-Causing Bacteria Relevant to Public Health - Karolis Krikštaponis; Jūratė Šiugždaitė; Rita Vaickelionienė; Vytautas Mickevičius; Birutė Grybaitė (Molecules, 2025)
The increasing number of antibiotic-resistant pathogens forces us to accelerate the search for new antimicrobial agents. Based on this, we chose to synthesize a library of 1-(2-hydroxy-5-methylphenyl)-5-oxopyrrolidine-3-carboxylic acid derivatives and evaluate their antibacterial activity against various pathogens. A series of (2-hydroxy-5-methylphenyl)-5-oxopyrrolidine-3-carboxylic acid and its hydrazide derivatives were prepared and identified by the methods of IR, 1H, and 13C NMR spectroscopy and a microanalysis technique. The resulting compounds were evaluated in vitro for their efficacy against the Gram-positive Staphylococcus aureus (ATCC 9144), Listeria monocytogenes (ATCC 7644), and Bacillus cereus (ATCC 11778) bacterial strains as well as the Gram-negative Escherichia coli (ATCC 8739) bacteria. Oxacillin, ampicillin, and cefuroxime were used as control antibiotics. Among the obtained compounds, hydrazone with a 5-nitrothien-2-yl fragment surpassed the control cefuroxime (7.8 μg/mL) against almost all strains tested. Hydrazone with a 5-nitrofuran-2-yl moiety showed a slightly lower but also potent effect on all bacterial strains. Moreover, hydrazone with a benzylidene moiety demonstrated very strong inhibition of S. aureus (3.9 μg/mL) in comparison with the antibacterial drug cefuroxime (7.8 μg/mL). In addition, some of these compounds exhibited remarkable bactericidal properties. In a complete biofilm disruption study, 5-nitrothienylhydrazone showed excellent results in disrupting S. aureus and E. coli biofilms. The test results show the potential of the newly obtained derivatives as a source of antibacterial agents. Therefore, further studies on the molecular optimization of these compounds are necessary for the development of new antibacterial drugs.